Kepemimpinan berorientasi instruksi dan kinerja guru di lembaga Raudhatul Athfal - Tarso Tarso; Umi Narimawati; Bobi Kurniawan (Curricula: Journal of Curriculum Development, 2026)
The improvement of educational quality in Raudhatul Athfal (RA) institutions depends heavily on leadership effectiveness and educators' competence in managing meaningful learning processes. This study examines the influence of learning-oriented leadership on teacher performance within RA institutions across Kulon Progo Regency. Employing a quantitative approach with an ex-post facto causal-correlational design, data were collected from 120 teachers using a saturated sampling (census) technique. The research instruments consisted of validated five-point Likert-scale questionnaires, and the data were analyzed using simple linear regression. Descriptive statistics indicate that both learning-oriented leadership and teacher performance range from moderate to high, although there are significant disparities across institutions. Dimensional analysis reveals that while direct learning facilitation is strong, external collaboration (boundary spanning) and child development assessment remain underdeveloped. Inferential statistics confirm a significant positive influence. These findings suggest that leadership prioritizing internal learning creates a supportive professional environment. This study recommends networking training for principals and assessment workshops for teachers to reduce educational quality disparities in the region.